Sex and Heart Failure Treatment Prescription and Adherence - Farrero, Marta; Bellumkonda, Lavanya; Gómez Otero, Inés; Díaz Molina, Beatriz (Frontiers in Cardiovascular Medicine, 2021)
Heart disease is the leading cause of death in both men and women in developed countries. Heart failure (HF) contributes to significant morbidity and mortality and continues to remain on the rise. While advances in pharmacological therapies have improved its prognosis, there remain a number of unanswered questions regarding the impact of these therapies in women. Current HF guidelines recommend up-titration of neurohormonal blockade, to the same target doses in both men and women but several factors may impair achieving this goal in women: more adverse drug reactions, reduced adherence and even lack of evidence on the optimal drug dose. Systematic under-representation of women in cardiovascular drug trials hinders the identification of sex differences in the efficacy and safety of cardiovascular medications. Women are also under-represented in device therapy trials and are 30% less likely to receive a device in clinical practice. Despite presenting with fewer ventricular arrythmias and having an increased risk of implant complications, women show better response to resynchronization therapy, with lower mortality and HF hospitalizations. Fewer women receive advanced HF therapies. They have a better post-heart transplant survival compared to men, but an increased immunological risk needs to be acknowledged. Technological advances in mechanical circulatory support, with smaller and more hemocompatible devices, will likely increase their implantation in women. This review outlines current evidence regarding sex-related differences in prescription, adherence, adverse events and prognostic impact of the main management strategies for HF.